Improvement in control and gain aspects of impedance source inverters and converters - Aleem, Zeeshan (Department of Electrical Engineering, 2019)
Power electronics have revolutionized the concept of power control for power conversion and for control of electrical motor drives. Power electronics has been extensively used in industrial applications since it was first discovered in 1902. Power conversion is one of the most important and prominent applications of power electronics. Impedance source networks cover the entire spectrum of electric power conversions from DC-AC (e.g. inverters), to phase and frequency conversion (AC-AC) in a wide range of applications. A wide variety of topologies and control methods using different impedance source networks have been presented in the literature to overcome the limitations and problems of traditional voltage source and current source as well as various classical buck–boost, unidirectional, and bidirectional converter topologies. Proper implementation of the impedance-source network with appropriate switching configurations and topologies reduces the number of power conversion stages in the system power chain, which may improve the reliability and performance of the power system. The main focus of this thesis is to study and analyze different impedance source inverters and their control methods, and the development of improved impedance source power systems that will comprise advanced circuitry and provide higher voltage gains needing less complex systems that together provide more cost-efficient solutions. The systems under considerations would have high frequency electrical isolation and voltage clamping across the DC-link inverter bridge that would resulting in better protection, lower overall system losses, and increased efficiencies. Then parallel techniques will be discussed, analyzed and implemented for the class of impedance source inverters. This parallel operation of ZSIs leads to reduced components stress across the inverter bridges by sharing the currents, interleaving, ease of maintenance, modularity, higher reliability, and (N+1) redundancy. The scope of impedance source networks is not limited to inverters (i.e., DC-AC power conversion), but covers a wide range of electric power conversion applications including (DC-DC and AC-AC converters). Thus, the last part of this research project will include the development of a new class of transformer based impedance source AC-AC converters with novel control strategies to increase the input to output gains and to improve the conglomerate characteristics of the AC-AC converters. Validation of the proposed structures will be done virtually using the Saber, PSIM simulations, and physically using experimental hardware prototypes. Several KW power systems will be fabricated and implemented using a DSP-kit based on the TMS320f28335 processor. Modified modulation schemes will be applied to control the switching of active devices. Furthermore, clamping techniques by minimizing the high frequency loop via clamping diode will be applied to the proposed inverters to limit the voltage overshoots caused by the leakage inductance energy. The better performance of improved impedance source network (with added benefits of HF isolation and parallelization) to design more resilient and efficient converter topology for various applications such as adjustable speed drives, distributed generation systems, super-capacitor energy storage systems, uninterruptable power supply, dc circuit breakers, electric vehicles, avionics, and electronic loads will attract researchers and professional engineers to explore it in depth.